Effects of changing farming practices in African agriculture - Rosenstock, Todd S.; Steward, Peter; Joshi, Namita; Lamanna, Christine; Namoi, Nictor; Muller, Lolita; Akinleye, Akinwale O.; Atieno, Erica; Bell, Patrick; Champalle, Clara; English, William; Eyrich, Anna-Sarah; et al. (Nature Portfolio, 2024)
Information on the effects of changing agricultural management on crop and livestock performance is critical for developing evidence-based policies, investments, and programs. Evidence for Resilient Agriculture (ERA) v1.0.1 presents a dataset that harmonizes and aggregates 112,859 observations from 2,011 agricultural studies taken place in Africa between 1934 and 2018. The dataset includes information on the effect of 364 combinations of management practices and technologies on 87 environmental, social, and economic indicators of outcomes. Observations are geolocated and temporally tagged and thus can be linked to other datasets such as historical weather, soil properties, and road networks. ERA offers a new resource for understanding the impacts of changing farming practices under diverse environmental contexts, providing data to support strategic interventions aimed to enhance productivity, resilience, and sustainability of African agriculture.